Diuretic 99mTc DTPA renography in assessment of renal function and drainage in infants with antenatally detected hydronephrosis - Radulović, dr Marija; Pucar, Dragan; Jauković, Ljiljana; Šišić, Marija; Krstić, Zoran; Ajdinović, Boris (Vojnosanitetski pregled, 2016)
Background/Aim. The controversy over the postnatal management of infants with antenataly detected hydronephrosis (ANH) still exists. We presented the results of diuretic 99mTc diethylenetriamine pentaacetic acid (DTPA) renography in 30 infants with the antenatal diagnosis of unilateral renal pelvic dilatation. The aim of this study was to assess the renal function determined by the pattern of drainage and split renal function (SRF) on diuretic renography and to correlate these findings with anteroposterior pelvic diameter (APD) estimated by ultrasonography. Methods. A total of 30 infants with 60 renal units (RU) (25 boys and 5 girls, median age 6.0 months, range 2–24) presented with unilateral hydronephrosis on ultrasound in the newborn period, underwent DTPA diuretic renal scintigraphy (F+15 protocol). The median APD evaluated on perinatal ultrasound was 15 mm (range 5–30). The postnatal associated clinical diagnosis were pelviureteric junction obstruction (PUJ), simple hydronephrosis, megaureter, vesicoureteral reflux (VUR) and posterior urethral valves in 11, 10, 6, 2 and 1 infant, respectively. Images and Tmax/2 after diuretic stimulation on the background subtracted renographic curves were used as the criteria for classifying the drainage as good, partial, and poor or no drainage. The SRF was calculated with the integral method. Results. Good drainage was shown in 36/60, partial drainage in 13/60 and poor or no drainage in 11/60 RU. The SRF > 40% was observed in 55/60 RU, with no RU showing SRF lower than 23.5%. In infants with severe ANH the obstruction was not excluded in 94.1%. Conclusion. Diuretic renography in antenatally detected hydronephrosis should be a useful tool in postnatal follow up, especially in differentiating nonobstructive hydronephrosis from obstructive. It is also importanat to assess and monitor the SRF. Our results suggest that even in the presence of partial or no drainage, SRF may not be significantly impaired. Key words: infant; hydronephrosis; prenatal diagnosis; radioistope renography